PENGARUH FISCAL STRESS TERHADAP KEMANDIRIAN FISKAL DAERAH DAN BELANJA MODAL (Studi Empiris: Pada Kabupaten Se-Jawa Tengah 2006 - 2012 Dominan Kontribusi Sektor Industri Non Migas) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims to describe and analyze the influence of Fiscal Stress for Fiscal Independence Regional Fiscal Stress effect on the growth of Capital Expenditures; Regional Fiscal Independence influence on the growth of Capital Expenditures and Fiscal Stress effect on capital expenditures through Regional Fiscal Independence. The research was conducted in 8 districts of Central Java Province dominant industry non migas sectors is Regency of Sukoharjo, Karanganyar, Kudus, Jepara, Semarang, Kendal, Batang and Pekalongan. The data used and the realization of the budget target of 2005 to 2012. Data obtained from the report government finance statistics published Central Java Central Agency of Statistics (Biro Pusat Statistik/BPS), Central Java. Then the normality test data and followed by linear regression analysis with a model of mediation. Fiscal Stress research found that direct negative effect on Regional Fiscal Independence (β=-0.323; sig=0.020 < α=5%). The negative path coefficients provide information if Fiscal Stress increases the reliance on central funds (Dana Alokasi Umum/DAU) decreases and vice versa if the Fiscal Stress decreases the dependence on central grants (Dana Alokasi Umum/DAU) is increasing. Fiscal Stress has positive and direct impact on Capital Expenditures (β=0.480; sig=0.001 < α=5%). This marked a positive path coefficients provide information if Fiscal Stress increases, Capital Expenditures increased and vice versa if the Fiscal Stress decreases the Capital Expenditures in decline. Fiscal Independence Regional positive and direct impact on Capital Expenditures (β=0.412; sig=0.002 < α=5%). This marked a positive path coefficients provide information if the Regional Fiscal Independence increases, capital expenditures increased and vice versa if the area decreases the Fiscal Independence Capital Expenditures also decreased. Fiscal Stress has a direct impact on Capital Expenditures and has no direct effect of -0.133. So overall Fiscal Stress affects Capital Expenditures through Regional Fiscal Independence of ​​0.347. This means the Regional Fiscal Independence variable is mediating variables (intervening). Keywords: Fiscal Stress, Fiscal Independence Regional and Capital Expenditures